Effects of strategic flukicidal (triclabendazole) treatment in naturally fasciola infected sheep: A case study in Wolemera District, Ethiopia - Asrat, M.; Petros, B.; Jobre, Y.; Peden, Donald G.; Shiferaw, Y.; Taddesse, G.; Mamo, M. (2005)
A one year (November 2003 to October 2004) trial was carried out to measure the effects of strategic flukicidal (triclabendazole) treatment regimes on some indicative parameter in naturally fluke-infected sheep in Wolemera District. . Three groups of animals were used in this experiment: Group I (n=23) received only single dose of triclabendazole (10mg/kg) at trial initiation; Group II (n=28) received two doses of triclabendazole treatments at an interval of 150 days; Group III (n=29) served as positive (untreated) control. Experimental animals were kept under traditional smallholder extensive management. Measured parameters include faecal egg output, PCV, body condition score and body weight gain and collection of samples were done at day 0, 21, 153, 172, 322. The presence or absence of variations of the measured parameters amongst experimental groups was analyzed using one-way ANOVA in a General Linear Model (GLM). The economic return from the strategic intervention was also computed. The results of the study revealed that statistically marked decrease (p<0.05) in mean feacal egg output (0.03±1.32), improved mean PCV levels (6.50±1.28), mean body weight gain (4.10±0.76) and mean body condition scores (0.57±0.09) in Group II animals. The corresponding values in animals receiving one-time treatment (Group I) were 0.35±1.55, 3.56±1.16, 0.90±0.73 and 0.17±0.08. The economic return from one and twice strategic triclabendazole treatments was 5.24/animal/year and 26.16 birr/animal/year. Untreated control animals showed negative weight gains, hence, no monetary return over the study year. Non-monitory benefits that smallholder farmers obtain from twice strategic anthelmintic treatments were highlighted. Future studies to assess the long-term effects of strategic anthelmentic treatments intervention in the highlands and replication of similar trials in mid-altitude and lowland sites, where the level of fasciolosis occurrence differ, are recommended.